Kvinnor + Försvarsmakten = Sant? - Perlaky,Charlotte (2020)
The aim of this study was to analyze the female under-representation in the Swedish Armed Forces in order to gain a deeper understanding of the organization’s underlying difficulties in recruiting and retaining women. By collecting a women’s experience of the Swedish Armed Forces via a web survey and applying a qualitative content analysis to investigate the respondents’ answers, the study wishes to see whether the theory of military masculinity can be used to explain the current underrepresentation of women in the organization. The result of the study showed that theory of military masculinity can be applied on the case of the Swedish Armed Forces and can thus be used to explain why the female representation in the organization remains low. In conclusion, the study argues that the presented hypothesis, which claims that the Swedish Armed Forces is not welcoming to women, to some extent is true. However, the unwelcoming environment may be due to the behavior of male colleagues, as well as the military culture and tradition of the military organization. The study answers its research question by arguing that the Swedish Armed Forces as a military organization is based on the male norm, therefore it does not have a reputation of being a workplace for women, which risks leading to women neither applying for the organization nor finding an interest in staying.
Keywords: the Swedish Armed Forces; military organization; military masculinity; hegemonic masculinity; masculinity; women